Dynamic Behaviour of a Nonlinear Gantry Crane System - Jaafar, Hazriq Izzuan; Mohamed, Zaharuddin; Jamian, Jasrul Jamani; Zainal Abidin, Amar Faiz; Anuar , Mohamed Kassim; Ab Ghani, Zailani (2013)
This paper presents investigations of dynamic behaviour of a nonlinear Gantry Crane System (GCS). The dynamic model is derived using Lagrange equation. Various system parameters of the system are tested to observe the actual behaviour of the dynamic model system. System responses including trolley displacement and payload oscillation are analyzed. Simulation is conducted within Matlab environment to verify the performance responses of the system. It is demonstrated that several factors affected the performances of the GCS in terms of input voltage, cable length, payload mass and trolley mass.